Compensation those affected by technological development risks within the scope - حسن, حيدر فليح; ارحيم, عبد الله احمد (Journal of Legal Sciences, 2019)
The unprecedented technological development the world witnesses nowadays has been providing brilliant medical service to the human being including examination, diagnosis and the treatment or  follow up.However , such works hide behind potential risks treating people's lives and such risks my be discovered within the limits of now –how and technical knowledge prevailing the time of rendering the medical service.So that pay attention, Also this the question is raised on how to keep up between the safety of the patients and such risks are being un known by the provider and questioning them contradicts the justices subsequently can the patients) acquire the compensation? The answer to such question is the basis of this researcher by divided it to requests having in first request  compensation by the state and the second request having compensation by national office for compensate.